Malaria Transmission Dynamics among Plantation Communities in Langkat District, North Sumatra: The Role of Household and Environmental Factors - Yenny Saraswati; Rahayu Lubis; Irnawati Marsaulina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Indonesia contributes nearly one-third of malaria cases in Southeast Asia (World Malaria Report 2023, 2023). In North Sumatra Province, Langkat Regency continues to report relatively consistent malaria incidence, particularly in forest fringe and plantation areas, although the absolute number of cases remains relatively low. A preliminary study conducted by (Nainggolan et al., 2022) identified several Plasmodium species in the region, including P. knowlesi, which is recognized as a cause of zoonotic malaria with long-tailed macaques serving as the natural host. The proximity of plantation habitats to forested areas increases the potential interaction among humans, vectors, and natural reservoirs of the disease, thereby facilitating cross-species transmission. This study aimed to analyze the factors influencing malaria incidence among plantation communities in Langkat Regency. This study employed an unmatched case-control design conducted from June to December 2025 in three selected healthcare facilities. Samples were collected using a consecutive sampling technique, consisting of 47 case groups and 94 control groups with a 1:2 ratio. Data were analyzed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis using multiple logistic regression. The results showed that living in the same household with malaria patients (household clustering) (OR=22.89; p=0.004), activity time (OR=3.584; p=0.004), and residential distance from mosquito breeding sites (OR=7.838; p=0.018) were significantly associated with malaria incidence. One of the mosquito breeding sites identified in this study was latex collection cups in rubber plantations. Plantation environments adjacent to forest areas may strengthen the potential for residual transmission and reflect a focal transmission pattern at the village or sub-district level. This study concludes that malaria incidence among plantation communities is influenced by a combination of behavioral and environmental factors. Therefore, integrated malaria control measures are required through environmental health improvement, vector control, enhancement of community preventive behaviors, and strengthening surveillance in plantation and forest fringe areas.